Long-term electrode–skin impedance variation for electromyographic measurements - Sousa, Andreia S. P. (2023)
This study aims to observe the evolution of the electrode–skin interface impedance of surface EMG electrodes over the time taken to determine the time of stabilization. Eight healthy subjects participated in the study. Electrode–skin impedance was evaluated in the rectus abdominal muscle every five minutes, over a total period of 50 min. A reduction of 13.23% in the impedance values was observed in minute 10 (p = 0.007), and a reduction of 9.02% was observed in minute 15 (p = 0.029). No statistically significant differences were observed in the other instants evaluated. The findings obtained in the present study demonstrate a decrease in electrode–skin impedance from minute 5 to minute 15, followed by a stabilization period with a low percentage of variation till minute 50.